npj Health Systems - Chen, Tony.; SpringerLink (Online service) (London : Nature Publishing Group UK : Imprint: Nature Portfolio.)
npj Health Systems is an interdisciplinary title covering all aspects of health systems research through high-quality interdisciplinary analysis of healthcare financing, delivery models, policy interventions, and their impacts on population health, equity, and outcomes. Main topics of interest will include: Health policy and practice - to cover healthcare policies, strategies, and interventions aimed at improving health systems performance, enhancing access to care, reducing disparities, and promoting population health. Implementation science - effective translation of research findings into policy and practice, including evaluations of implementation strategies, barriers, facilitators, and outcomes. Global Health Systems - studies examining health systems in various global contexts, including LMICs (Low- and Middle-Income Countries), with a focus on challenges, innovations, and best practices in healthcare delivery and management. Quality Improvement and Patient Safety - studies aimed at enhancing the quality, safety, and effectiveness of healthcare delivery systems, including efforts to reduce medical errors, improve clinical outcomes, and enhance patient experiences. Health Information Technology - research on the role of technology in health systems, including EHRs, telemedicine, health information exchange, and digital health innovations, and their impact on healthcare delivery and patient outcomes. Education and Training - studies focused on education, training, and workforce development initiatives aimed at strengthening health systems capacity, enhancing the skills of healthcare professionals, and improving the delivery of care. Ethics and Equity - studies looking at the ethical considerations, social determinants of health, health equity, and disparities in healthcare access and outcomes, with a focus on promoting fairness, justice, and human rights within health systems Financing and Healthcare Models - dedicated to research on financing health systems and different models of healthcare, whether private, public, or hybrid. This could also include health insurance, payment reforms, costs and personal expenditure, and health economics.
Keywords: Medical sciences; Health Sciences